LITERATURE REVIEW: ANALYSIS OF SOCIAL MEDIA USAGE INTENSITY AND INCIDENTS OF DEPRESSION AND ANXIETY AMONG UNIVERSITY STUDENTS - Rachma, Erica Feby; Eka Sari, Jayanti Dian; Dwiyanti, Endang; Zuhro, Andina Fatimatus (Journal of Community Mental Health and Public Policy, 2025)
Background: Easy access to communication and information can lead to prolonged social media use, which increases the risk of depression and anxiety. Purpose: To analyze social media usage intensity on depression and anxiety among university students. Methods: A literature review was conducted by retrieving articles from PubMed, ResearchGate, and Google Scholar databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method was used for article selection. Quality of the articles was assessed using The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for analytical cross-sectional studies. Results: The articles classified into three categories: six articles focused on depression, with four reporting statistically significant correlation; three articles on anxiety, all of which showed significant correlation; and two articles investigated both depression and anxiety, with one reported significant correlation for both variables and the other specifically for anxiety. Conclusion: Prolonged social media exposure leads to increased engagement with diverse online content, fostering self-comparison and consequently depression and anxiety. These findings emphasize the importance of higher education institutions implementing self-regulation interventions, such as self-control training programs, to mitigate adverse mental health outcomes among university students. Abstrak Latar Belakang: Media sosial dengan manfaatnya memberikan sarana dalam menjangkau informasi, memperluas jaringan sosial, mengekspresikan diri atau hiburan. Namun, penggunaannya yang melampaui batas dapat mengakibatkan depresi maupun kecemasan. Tujuan: Menganalisis intensitas penggunaan media sosial terhadap kejadian depresi dan kecemasan pada mahasiswa. Metode: Tinjauan literatur yang diambil dari database PubMed, ResearchGate dan Google Scholar. Pencarian artikel menggunakan metode Preferred Reporting Items for Systematic Review & Meta-Analyses (PRISMA). Kualitas artikel yang dikaji dinilai berdasarkan JBI (The Joanna Briggs Institute) Critical Appraisal Checklist untuk analisis studi cross-sectional. Hasil: Berdasarkan sebelas artikel yang dikaji, terbagi menjadi tiga kategori: enam artikel berfokus pada variabel depresi, dengan 4 artikel menunjukkan hubungan dan 2 artikel tidak; tiga artikel membahas kecemasan, seluruhnya menunjukkan hubungan; serta dua artikel menganalisis depresi sekaligus kecemasan secara bersamaan dengan satu artikel menunjukkan hubungan kedua variabel dan satu artikel hanya menunjukkan hubungan dengan kecemasan. Kesimpulan: Lamanya pengoperasian media sosial selaras dengan lamanya terpapar bermacam informasi dari media sosial yang memungkinkan penggunanya membandingkan diri dengan orang lain. Temuan ini menggarisbawahi pentingnya institusi perguruan tinggi menerapkan intervensi regulasi diri seperti program pelatihan kontrol diri pada mahasiswa, sehingga dampak negatif media sosial dapat dikurangi.